LITERATURE ON THE RELATIONSHIPS BETWEEN ORGANIZATIONAL PERFORMANCE AND EMPLOYEE JOB SATISFACTION - Abbod Altamimi, Abbod Naseb (Archives of Business Research, 2019)
Employee job performance is identified as one of the most important components in measuring a company’s efficiency implying that employee high performance reduces organizational production cost. This is mostly observed in organizations where employees are satisfied with their jobs. In view of this, extensive research has been conducted with the aim of exploring the relationships between employee job satisfaction and performance of organizations so as to determine if there is any empirically provable relationships between employee job satisfaction and organizational performance, and vice versa. The results of some of these studies showed the existence of a clear link between employee job satisfaction and organizational performance in both directions. The relationship tends to be stronger from employee job satisfaction to organizational performance rather than from organizational performance to employee job satisfaction. Therefore the purpose of this study is to look into the indicators or factors that influence the two-way relationships between employee job satisfaction and organizational performance.